Corrective Taxation for Curbing Pollution and Promoting Green Product Design and Recycling - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this paper we consider a competitive economy with flows of materials from extraction via recycling to landfilling which exhibits distortions due to pollution, external landfilling costs and inefficient product design. The allocative impact of tax-subsidy policies aiming at internalizing the distortions are analyzed when the pertinent tax-subsidy rates were successively raised from zero toward their efficiency restoring levels. Promoting recyclability by greening the product design stimulates recycling as expected. But it also increases primary material extraction and - possibly - the total waste flow, and it reduces the recycling ratio.
Keywords: 330; Green design; pollution; recycling; material